Patient preferences regarding the dress code, conduct and resources used by doctors during consultations in the public healthcare sector in Bloemfontein, Free State - J. W. van der Merwe; M. Rugunanan; J. Ras; E-M Röscher; B. D. Henderson; G. Joubert (South African Family Practice)
Background: The doctor–patient relationship is important in determining the quality of healthcare provided. This study aimed to identify patient preferences regarding dress code, conduct and resources used by doctors during consultations in the public healthcare sector, Bloemfontein. Information from this study can be of benefit in determining policies and dress codes within hospitals and medical schools.